Integrating drug effects on individual cardiac ionic currents and cardiac action potentials to understand nonclinical translation to clinical ECG changes - Johannesen, Lars; Abi-Gerges, Najah; Sweat, Katrina; Roup, Ana; Page, Guy; Baron, Claudia Alvarez; Yu, Huimei; Wu, Wendy W. (Frontiers in Pharmacology, 2025)
Concomitant inhibition of the late Na+ current (INaL) and/or the L-type Ca2+ current (ICaL) has been hypothesized to mitigate hERG block-mediated QTC prolongation. This hypothesis was tested in a clinical trial using drugs selected based on available patch clamp data at the time. The results showed that hERG block-mediated QTC prolongation with dofetilide was shortened by co-administration of lidocaine or mexiletine–drugs that inhibit INaL. However, diltiazem, selected as the preferential ICaL inhibitor, did not shorten hERG block-mediated QTC prolongation by moxifloxacin. Patch clamp results can be sensitive to experimental differences across laboratories. Therefore, this study reexamined the effects of all drugs on INaL, ICaL, and hERG current using overexpression cell lines and physiologically relevant experimental protocols aimed at producing drug-channel interaction characteristics in humans. Drug effects on ventricular action potentials (APs) from adult human trabeculae were also tested to better understand the nonclinical and clinical findings. Mexiletine and lidocaine showed similar potencies on inhibiting INaL and ICaL in the prior and present patch clamp studies. Both drugs reduced dofetilide-induced AP duration (APD) prolongation, consistent with the clinical data. For diltiazem, the ICaL potency and the separation between ICaL and hERG potencies (ICaL: 1.3 µM; hERG: 8.9 µM; hERG-to-ICaL ratio = 7) is much reduced comparing to the prior results (ICaL: 112.1 nM; hERG: 6.6 µM; ratio = 59). These new findings are consistent with diltiazem-induced APD shortening and AP triangulation caused by greater reductions in the early rather than late repolarization–a signature of multi-ion channel block. Consistent with this interpretation, nifedipine, which preferentially inhibits ICaL over hERG (ICaL: 13.2 nM; hERG: 35 μM; ratio = 2,651) caused APD shortening without AP triangulation. Results from this study thus support the following: 1) diltiazem failed to reduce moxifloxacin-induced QTC prolongation due to its concomitant hERG block at clinical exposure levels; and 2) the importance of using physiologically relevant protocols to generate ion channel pharmacology and obtaining functional recordings from myocytes to provide a better understanding of nonclinical data translation to clinical ECG signals. Data used in this manuscript, including the original electrophysiology records, may be found at: https://osf.io/69ght/.